A Porphyromonas gingivalis Mutant Defective in a Putative Glycosyltransferase Exhibits Defective Biosynthesis of the Polysaccharide Portions of Lipopolysaccharide, Decreased Gingipain Activities, Strong Autoaggregation, and Increased Biofilm Formation - Yamaguchi, Mikiyo (American Society for Microbiology (ASM), 2010)
The Gram-negative anaerobic bacterium Porphyromonas gingivalis is a major pathogen in periodontal disease, one of the biofilm-caused infectious diseases. The bacterium possesses potential virulence factors, including fimbriae, proteinases, hemagglutinin, lipopolysaccharide (LPS), and outer membrane vesicles, and some of these factors are associated with biofilm formation; however, the precise mechanism of biofilm formation is still unknown. Colonial pigmentation of the bacterium on blood agar plates is related to its virulence. In this study, we isolated a nonpigmented mutant that had an insertion mutation within the new gene PGN_1251 (gtfB) by screening a transposon insertion library. The gene shares homology with genes encoding glycosyltransferase 1 of several bacteria. The gtfB mutant was defective in biosynthesis of both LPSs containing O side chain polysaccharide (O-LPS) and anionic polysaccharide (A-LPS). The defect in the gene resulted in a complete loss of surface-associated gingipain proteinases, strong autoaggregation, and a marked increase in biofilm formation, suggesting that polysaccharide portions of LPSs influence attachment of gingipain proteinases to the cell surface, autoaggregation, and biofilm formation of P. gingivalis.